The Determinants of a Successful Family Business Succession - Christina Eka Prillia; Sarwo Edy Handoyo (Sultan Publisher, 2023)
Majority of business in Indonesia is family business firm. In fact, according to Daya Qarsa Research Firm in 2022, family businesses have contributed about 80% to Indonesia’s GDP as well as 40% to Indonesia’s market capitalization. However, most of the family businesses start to falter during the second generation and doesn’t last until the third generation. This article aims to determine 1) the influence of succession planning on family business succession, 2) the influence of family relationship on family business succession, 3) the influence of entrepreneurial spirit on family business succession, 4) the influence of intergeneration managerial mindset on family business succession. The method used to collect data in this study is online question form with google-form questionnaire with a total sample of 37 respondents. The data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS as the data processing tool. The samples in this study are family business successors in Gorontalo. The result of this study is 1) succession planning has an influence on family business succession, 2) family relationship has an influence on family business succession, 3) entrepreneurial spirit has an influence on family business succession, 4) intergeneration managerial mindset has no influence on family business succession.